IMPACT OF DIFFERENT ORGANIC AND INORGANIC AMENDMENTS ON GROWTH AND YIELD OF MUNG BEAN IRRIGATED WITH TEXTILE EFFLUENTS - UMAIR, M; SHAH, SAH; JAMEEL, R; ULLAH, S; NAZ, A; HAMID, S; FAIZ, A; RABNAWAZ, .; NAWAZ, S; AZIZ, S; et al. (Biological and Clinical Sciences Research Journal, 2024)
Water is an important substance for all life on earth, and it is essential for human beings, financial improvement, and the existence of ecological units. The quality and quantity of the water supply is very important, especially during irrigation. Due to the extensive measurement of water and colour associated with the manufacturing process, textile printing, and dyeing production lines around the world pose a major environmental risk. Textile wastewater contains a lot of pollutants including pH, temperature, shade, COD, BOD, TSS, TDS, EC, and heavy metals. This textile runoff continues to irrigate agricultural land, causing contamination of soils and plant systems with heavy metals. Therefore, adding organic and inorganic modifiers to soil is an effective technique for fixing heavy metals. Irrigate pots with textile wastewater of selected concentrations (10%, 25%, 50%, and 100%) collected in specific industrial sectors. The parameters of vegetative growth are reduced by increasing the concentration of textile effluent. Note the substantial reduction in the growth of plants applying wastewater at 100% concentration. In the case of T5, a significant increase in growth parameters was observed, where only tap water was used to pressurize the sludge, while dilute wastewater also enhanced growth at concentrations of 10% and 25%. For the chlorophyll content of mung bean plants, when the wastewater concentration is 100%, the recorded decrease is greater, followed by 10% and 25% respectively. The presence of heavy metals in wastewater reduces plant growth. In the experiment, all four treatments contained organic amendments (pressed sludge, poultry manure, biogas slurry, and farmyard manure). The other four treatment methods are pressure treatment of textile wastewater and the amount of organic modifier is 2%. By adding a correcting agent, the utilization rate of Cr is reduced, as the correcting agent will increase the pH of the soil, thus reducing the solubility of the metal. In addition, Cr can form insoluble complexes with organic materials, thus reducing its solubility.